STUDI LITERATUR PEMANFAATAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SEKOLAH DASAR - Dedi Nababan, Suwitno; Subali, Bambang; Ellianawati, Ellianawati; Edy Mulyono, Sungkowo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the extent to which the Problem-Based Learning (PBL) model is utilized to improve students' mathematical problem-solving skills at the elementary school level. The PBL model is a learning model oriented toward presenting problems that implicate critical and analytical thinking skills in dealing with issues related to the taught learning material. The method used in this study is library research. In its approach, this study applies a qualitative method where data collection is conducted through a literature review, focusing on searching scientific articles relevant to the research context. After analyzing the articles and journals, it was found that the implementation of the Problem-Based Learning (PBL) model has a positive impact on improving mathematical problem-solving skills at various levels of elementary school, both in lower and higher grades. In its application, the Problem-Based Learning (PBL) model affects students' ability to solve mathematical problems related to problem solving skills, and also strengthens teamwork and communication. These findings support previous research indicating that the implementation of the PBL model is effective in honing elementary school students' mathematical problem-solving skills, while also significantly optimizing their academic achievement.